IPO underpricing and overpricing and long-term firm performance in the Netherlands, United Kingdom, France, Sweden, and Italy: Learning from three Dutch IPOs - Timothy Drooduin (The Central European Review of Economics and Management (CEREM), 2023)
Aim: This research contributes to the study of the relationship between initial public offering (IPO) under- and overpricing and long-term firm performance as measured by net income. Research methods: Using ordinary least-squares regressions, an international sample of 444 IPOs from the United Kingdom, Sweden, France, Italy, and the Netherlands for the period 2013-2017 is analysed. The data was extracted from the Eikon Refinitiv database. Further, an in-depth analysis of three Dutch IPOs by six interviews with five (former) management members and one investment banker is conducted. Conclusions: The results show that the more profitable a firm is in the long run, the likelier positive initial stock returns move towards zero after the first trading day. The case studies support these findings and the concept of asymmetric information between market participants can offer a partial explanation. Additionally, as firms operating in the industrial and healthcare sector grow larger, the offer price tends to be closer to the overall market demand. Nonetheless, no significant relationship is found between initial stock return and net profitability for other industries. While the country analysis also displays no significant relationship, underpricing is more prevalent in the United Kingdom than in the other sample countries. Originality: This article combines a full-fledged quantitative study with a full-fledged qualitative study on one of the most perilous corporate finance milestones, that is, the complex transformation from a private to a public company through a stock market listing. Limitations: The sample composition skews towards underpriced IPOs. Also, although the notion of reverse causality is discussed based on the views of interviewees, no quantitative evidence is provided.
Keywords: G32; 330; Initial public offering; equity pricing; firm performance; capital markets; case studies